Rare Books in Syria A Study of Essence & Standards - عمران, ينل (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study tends to crystallize the concept of rare books together with surveying a practical study of their reality in Syria in addition to probing their dimensions within the spaciotemporal frame and statistical control. The researcher, however, adopts the descriptive method in her case study, which handles one single case per se, in an attempt to pinpoint quintessentially the issue under study. This study concludes with a few interesting points, such as: the findings show the non-existence of a precise and accurate definition to the term rare books. Findings also reveal that ancient rare books in Syria could be identified within the period 1706-1929, and the number of books reached 1211. In brief, the study concludes with the fact that Syria has been the first Arab country unprecedented in the publishing world since 1706. This study recommends the necessity to simultaneously proceed the project of digitizing rare books in Syria, and to work hard to collect the rare books scattered over Syrian geography. This is so via issuing a law that simulates the legitimizing legal submission, and preparing indexes that control rare books in Syria, since this is a part and parcel of the intellectual product that represents the national memory providing that such a process is redeemed accessible and timely controlling such rare books.